Feminist precursors of mutual support groups in the mad movement: a historical-critical analysis - Grecia Guzmán Martínez; Margot Pujal i Llombart; Enrico Mora Malo; Dau García Dauder (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
Mutual support groups are one of the most important collective actions in the psychiatric survivors movement or mad movement. Among its precursors, different proposals from social movements and community perspectives on collective health have been mainly well-known. In this article we carry out a historical overview of their antecedents, pointing out different actions from the Women's Liberation Movement and the Women's Health Movement. From this, we perform a critical analysis considering three axes to understand the emergence of collective actions in mental health: personal experience in relation to the sociopolitical structure; the construction of political subjects in this field; and power relationships in the management of madness and psychological discomfort. We show how mutual support groups, in the context of the mad movement, give continuity to the trajectories of collective and feminist health actions, and are positioned as tools for the creation of political processes in different sociocultural contexts.